Policy Assignment Strategies with Somewhat Flexible Exchange Rates Policy. (IMF Working Papers; Working Paper ;, 1988)
The choice of assigning monetary or fiscal policy to external balance is complicated when the authorities are concerned with both the current account balance and the exchange rate. A strategy of using monetary policy to control the current account via the exchange rate may fail, because the relative-price effect is likely to be offset by the effect of monetary policy on aggregate demand. An alternative strategy, in which fiscal policy is assigned to limit shifts in the current account while the exchange rate is not directly targeted, may have a better chance of having favorable effects on both variables.